2009
DOI: 10.4103/0970-2113.48897
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and patient gender: An analysis and its implications in tuberculosis control

Abstract: Objective:To analyze the profile of pulmonary tuberculosis patients with respect to gender and its implications in tuberculosis control. Setting: DOTS center at a tertiary, teaching hospital in South India.Materials and Methods:A retrospective study was undertaken by screening medical records of 446 patients with pulmonary tuberculosis. Data studied included age, gender, and sputum smear status. Patients with comorbid conditions were excluded. No other data were considered.Results:The male to female ratio in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
25
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 1 publication
(1 reference statement)
11
25
1
4
Order By: Relevance
“…Although male infection in present study was predominant, female ratio could not be representing the actual situation because many women do not attend official health care centers due to fear from social stigma with fear from probable consequence of it like divorce, the present finding is in concurrence with other reports [24,25] that proposed this ratio could be attributable to biological characteristics and socioeconomic and cultural barriers to access healthcare.…”
Section: Discussionsupporting
confidence: 84%
“…Although male infection in present study was predominant, female ratio could not be representing the actual situation because many women do not attend official health care centers due to fear from social stigma with fear from probable consequence of it like divorce, the present finding is in concurrence with other reports [24,25] that proposed this ratio could be attributable to biological characteristics and socioeconomic and cultural barriers to access healthcare.…”
Section: Discussionsupporting
confidence: 84%
“…This result is in corresponds with other studies. [13][14][15] However, present study showed that there was no significant association of both age and gender wise distribution with pattern of pulmonary tuberculosis. On smoking-wise distribution, smokers were found more susceptible to pulmonary tuberculosis than non-smokers which was in accordance with other studies.…”
Section: Discussionmentioning
confidence: 63%
“…6,13 Since this age group people are highly active, their chance of exposure is also high which support evidence of acquiring disease. On gender wise distribution, 10 (25%) female patients and 27 (27.55%) male patients were diagnosed with pulmonary tuberculosis (PTB).…”
Section: Discussionmentioning
confidence: 90%
“…The epidemic of TB in terms of sex has changed as a result of the HIV epidemic. Before the era of HIV the male-to-female ratio for TB incidence was 2:1, [20] but the high prevalence of HIV in females has led to an increased incidence of TB among females. [21] A number of studies and reports have shown that women of childbearing age were more likely than the older women to develop TB due to co-infection with HIV.…”
Section: Discussionmentioning
confidence: 99%